Dietary pyridoxine potentiates thermal tolerance, heat shock protein and protect against cellular stress of Milkfish (Chanos chanos) under endosulfan-induced stress. (August 2016) - Kumar, Neeraj; Ambasankar, K.; Krishnani, K.K.; Kumar, Prem; Akhtar, M.S.; Bhushan, Shashi; Minhas, P.S.
Abstract: We herein report the protective role of pyridoxine in enhancing thermal tolerance of Milkfish Chanos chanos reared under endosulfan-induced stress. Four isocaloric and isonitrogenous diets were prepared with graded levels of pyridoxine (0, 50, 75 and 100 mg/kg). Two hundred and twenty five fishes were randomly distributed into four treatment groups in triplicate, reared under endosulfan-treated water, which were fed with pyridoxine supplemented diet, while the negative control group was reared without endosulfan-treatment and control fed. The concentration of endosulfan in treated water was maintained at a level of 1/40th of LC50 i.e. 0.52 μg/L. Dietary pyridoxine supplementation had significant (p < 0.01) effect on temperature tolerance viz. CTmax (Critical temperature maxima), LTmax (Lethal temperature maxima), CTmin (Critical temperature minima) and LTmin (Lethal temperature minima) of milkfish. The positive correlation was observed between CT max and LTmax (Y = −1.54 + 15.6x, R 2, 0.943) as well as CTmin and LTmin (Y = −1.44 + 1.021x, R 2, 0.941). At the end of the thermal tolerance study, antioxidative status and HSP 70 were significantly reduced in pyridoxine supplemented groups, whereas brain AChE was significantly (p < 0.01) elevated compared to positive and negative control. It is concluded that CTmax, LTmax, CTmin and LTmin, antioxidative status, neurotransmitter enzyme and HSP 70 strengthened the enhancement of thermal tolerance of Milkfish. Highlights: The dietary pyridoxine enhanced thermal tolerance of Chanos chanos reared under low dose endosulfan stress. The critical thermal minima and lethal minima were significantly influenced through pyridoxine supplementation. Dietary pyridoxine protect against oxidative stress reared under low dose endosulfan stress for five weeks. It's also protect neurotransmitter enzymes (AChE).